When Your Thyroid Causes Muscle Paralysis - Gandhi, Anand (J Endocr Soc, 2021)
Background: Periodic paralysis represents a spectrum of disorders characterized by ion channel dysfunction, mainly Na-K-ATPase channels. Thyrotoxic periodic paralysis (TTP) is defined by the presence of hypokalemia and diffuse muscular paralysis in a pre-existing hyperthyroid state. Diagnosis can be challenging, especially in cases of undiagnosed hyperthyroidism due to the non-specific presentation of this illness. We present a case of a young male who presented with recurrent, spontaneous paralysis found to have Graves’ disease. Clinical Case: A 38-year-old Asian male presented with sudden onset diffuse weakness, numbness, and tingling. The weakness was so severe that he could barely walk more than a few steps. However, his symptoms resolved in less than 24 hours without any intervention. Five months later, the patient experienced a recurrent episode of this similar constellation of diffuse muscle weakness and paresthesia. The patient was taken to a nearby hospital, where he was provided with intravenous fluid resuscitation. Initial laboratory workup was notable for hypokalemia to 1.4 mmol/L (n: 3.6 - 5.3 mmol/L), hypophosphatemia to 0.6 mmol/L (n: 2.4 – 4.8 mmol/L), and elevated creatinine kinase to 807 U/L (n: 22 – 198 U/L). Additionally, TSH was <0.001 mU/L (n: 0.45 – 4.5 mU/L) along with free T4 3.4 ng/dL (n: 0.80 – 1.70 ng/dL. The patient denied any other symptoms or a family history of similar symptoms. Lumbar puncture and brain/spine MRIs were unremarkable. Symptoms gradually improved throughout hospitalization with fluid and electrolyte repletion. Hyperthyroidism was treated with methimazole 5mg twice daily, later changed to PTU 50mg every eight hours due to recurrent headaches. Thyroid uptake scan showed diffuse bilateral uptake to 39.11% at 4 hours and 61.8% at 24 hours. Follow up labs revealed: TSH 0.3 mU/L, free T4 1.44 ng/dL, free T3 3.5 pg/mL (n: 2.3 – 4.1 pg/mL). Patient denied recurrent episodes of weakness or paresthesia. Definitive hyperthyroidism treatment with RAI was planned. Conclusions: The prevalence of TPP is higher in Asian males compared to other ethnic groups. TPP manifests as a sporadic onset of muscle weakness ranging from mild weakness to flaccid paralysis. It has been described that thyroid hormone itself augments the activity of the Na-K-ATPase channel and increases its responsiveness to beta-adrenergic stimulation. In addition, hyperthyroidism is associated with insulin resistance leading to hyperinsulinemia. Both beta-agonism and insulin promote potassium to be driven into cells resulting in hypokalemia. As such, activities which increase beta adrenergic stimulation, like stress and exercise, and promote the secretion of insulin, such as heavy carbohydrate intake, are well described triggers of TPP. Treatment revolves around acutely treating hypokalemia followed by preventing subsequent attacks via regulation of the altered thyroid state.